Promoting Student Ownership of Learning Through High-Impact Formative Assessment Practices - Susan M. Brookhart; Connie M. Moss; Beverly A. Long (The Evaluation Center at Western Michigan University, 2009)
The most important instructional decisions, those with the greatest influence on student success, are made by learners themselves (Stiggins, 2008). Formative assessment, done well, contributes to student ownership of learning more than any other classroom-based instructional or assessment practice (Bloom, 1984). It is an economical, highly effective, and uniquely flexible method that can improve learning (Leahy, Lyon, Thompson, & Wiliam, 2005). Simply put, the teacher's purpose in formative assessment is to give students the means, motive, and opportunity to take control of their own learning. And, through their involvement in formative assessment, students develop self-efficacy for specific learning and, more generally, they develop skills that contribute to increased self-regulation and self-assessment of learning. In order for students to be meaningfully involved in formative assessment, they must be guided by teachers who hold the beliefs, knowledge and skills that engender active student engagement in the learning process. This paper highlights interim findings from a five-year professional development initiative involving the Armstrong School District, a large, rural school district in Western Pennsylvania, and the Center for Advancing the Study of Teaching and Learning at the Duquesne University School of Education. The initiative rests on the fusion of formative assessment, teacher-student communication, and student ownership of learning. The professional development program employs online modules, peer study groups, classroom walkthroughs, and teacher inquiry into their classroom practices and the beliefs that drive them. The program explores seven formative assessment components: 1) Identifying and Clearly Communicating Learning Targets, .) Feedback that Feeds Forward, 3) Student Goal-Setting, 4) Student Self- Assessment, 6) Strategic Questioning, and 7) Formative Discourse. All components are linked to specific aspects of student motivation: intrinsic motivation, self-efficacy, self-regulation, goal-setting, and student attributions. The paper describes the impacts of formative assessment on student ownership of learning, student achievement, motivation, and active engagement as well as provides insights into teachers' experiences with student involvement. Findings show that not only have the teachers come to value and promote student ownership of learning using high impact formative assessment strategies, but that their efforts have resulted in high student engagement in learning and increased student achievement.